Gen Z and Millennials' Creative Solutions for Integrated Marketing Communication for Ancol Gondola Amusement Rides in 2025 - Bima Petala Rifardhi; Rosmawaty Hilderiah Pandjaitan; Afdal Makkuraga Putra (Journal of Social Research, 2025)
The Ancol Gondola is a cable car entertainment ride at Taman Impian Jaya Ancol, but since 2021 there has been a decrease in the number of visitors.  According to data from the General Election Commission (KPU) in 2024, currently the number of Gen Millennials in Indonesia is around 66 million people (33.60%) and Gen Z is around 44 million people (22.85%). Therefore, it is important for Gondola Ancol to know what and how  Gen Z and Millennial creative solutions for integrated marketing communication for Gondola Ancol in 2025. The purpose and purpose is, to uncover and explain, as well as find "what and how" forms of creative solutions from Gen Z and Millennials for integrated communication of the Ancol Gondola amusement ride in 2025. This qualitative research in the Constructivist paradigm uses Computed-Media Communication (CMC) theory, Innovation Diffusion Theory, and Interaction Engagement, as analytical tools. Case studies of intrinsic types are the method in this study. Presenting 10 informants from Gen Millennial and Gen Z with semi-structured in-depth interview techniques and also participatory observation. The result: the form of creative solutions for Gen Z and Millennials for integrated communication for the Ancol Gondola amusement ride in 2025, namely: According to Gen Z, the importance of strengthening information media or marketing communication through digital channels follows the latest trends. More adaptive and engaging product updates. Creative solutions can be such as: updating the architectural and functional design side, for example thematic events in the form of installation exhibitions, and coffee spots in the Ancol Gondola area. The importance of strengthening social media content packaging to increase public awareness or knowledge information about the Ancol Gondola itself. Maximizing online and offline advertising media to attract more audiences. There are obstacles to implementation for creative solutions for Gen Z and Millennials such as: One, according to Gen Z, the lack of development of a more expansive digital marketing strategy, the lack of differentiators and product refreshment that has a unique point, and the lack of product maintenance.; Two, according to Gen Millennials, lack of infrastructure in market approaching .